2010
DOI: 10.1080/00224490903216755
|View full text |Cite
|
Sign up to set email alerts
|

HIV Transmission Risk at a Gay Bathhouse

Abstract: Previous research found up to 14% of men who go to bathhouses engage in unprotected anal intercourse (UAI) and tend to have multiple sexual partners during their bathhouse visit, thus appearing to support concerns that such venues could foster acute outbreaks of new HIV infections. We conducted a two-stage probability sample of men exiting a gay bathhouse and focused our analysis on whether the partnering patterns of the men who engaged in UAI present such a risk. Among patrons who had oral or anal sex during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…This finding is consistent with prior research, which showed that MSM who seek sex online or in bathhouses tend to have a high number of sexual partners and a high rate of unprotected anal sex (Binson, Pollack, Blair, & Woods, 2010;Liau, Millett & Marks, 2006;Reidy et al, 2009;Woods et al, 2007). Moreover, our findings reveal that those who use both bathhouses and the internet to seek sex and those who use bathhouses only to seek sex are more likely to have prior HIV and STI testing, casual sex and a higher number of sex partners when compared to those who use only the internet to seek sex.…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with prior research, which showed that MSM who seek sex online or in bathhouses tend to have a high number of sexual partners and a high rate of unprotected anal sex (Binson, Pollack, Blair, & Woods, 2010;Liau, Millett & Marks, 2006;Reidy et al, 2009;Woods et al, 2007). Moreover, our findings reveal that those who use both bathhouses and the internet to seek sex and those who use bathhouses only to seek sex are more likely to have prior HIV and STI testing, casual sex and a higher number of sex partners when compared to those who use only the internet to seek sex.…”
Section: Discussionsupporting
confidence: 92%
“…It is useful to consider the pattern of results in the context of previously published data about sexual risk behavior inside this bathhouse (Binson et al, 2010; Woods et al, 2007). Fewer than 14% of patrons reported any UAI during their visit, and the rate of UAI was more than 3 times higher among HIV-positive men (28%) than among non-positive men (8%) (Woods et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Fewer than 14% of patrons reported any UAI during their visit, and the rate of UAI was more than 3 times higher among HIV-positive men (28%) than among non-positive men (8%) (Woods et al, 2007). This disparity suggests seroadaptive behaviors like serosorting and seropostioning (Snowden, Raymond, & McFarland, 2009) are being employed, although in the largely anonymous bathhouse context a partner’s serostatus is less likely to be known and more likely to be attributed based on the kind of sexual behavior he is willing to engage in (Binson et al, 2010). Among non-positive men who engage in anal intercourse during their bathhouse visit, the insertive UAI rate (18%) was more than double the rate for receptive UAI (8%) (Binson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One such group accessing social media is individuals at risk of HIV/AIDS (Kelly, 2004). Health workers have traditionally delivered information on HIV/AIDS education and prevention in physical locations such as bathhouses and clubs (Binson, Pollack, Blair, & Woods, 2010). However, the Internet is increasingly being used as a venue where individuals at risk of HIV/AIDS may meet others with low social risk of negative social consequences, access information, and form social relationships (Chiasson et al, 2007;Rhodes, 2004).…”
Section: Social Media and Hiv/aids Education And Preventionmentioning
confidence: 99%